Oil Rent, Geopolitical Risk and Banking Sector Performance - Alsagr, Naif; Almazor, Stefan F. Van Hemmen (International Journal of Energy Economics and Policy, 2020)
This paper aims to assess and compare the impact of geopolitical risk (GPR) on the banking sector profitability of "oil and nonoil dependent" emerging markets. For empirical estimation, we used annual macro-level data of all the countries listed in the GPR index from the period 1998 to 2017. The results of the fixed effect model indicate a negative significant impact of GPR on banking sectors’ profitability. Additionally, the results highlight the significant weakening moderation role of oil rent in the negative impact of GPR on the banking sector profitability. Multiple contributions arise from this study: Firstly, it explains and compares the impact of geopolitical risk on the banking sector profitability in non-oil-dependent. and oil-dependent economies. Secondly, our study sheds the light on the moderation effect of oil rent in the relationship between geopolitical risk and banking sector profitability. Indeed, the oil ”curse or blessing” argument was neither revealed nor clarified in the relevant literature. Keywords: Geopolitical Risk, Banking Sector Profitability, Oil Rent, Oil Dependent, Nonoil Dependent, Emerging Markets. JEL Classifications: Q4; G21; P48. DOI: https://doi.org/10.32479/ijeep.9668